Mortalidad perinatal en gestaciones múltiples: Hospital Miguel Servet, Zaragoza, España: 2000-2009 - Esther Cruz G; Raquel Crespo E; Yasmina José G; Pilar Andrés O; María Lapresta M; Javier Tobajas H (Permanyer, 2011)
Objetivos: Evaluar la mortalidad perinatal (MP) de las gestaciones múltiples del Hospital Miguel Servet de Zaragoza (2000-2009). Método: Análisis, sobre un total de 44.401 recién nacidos (RN) >500 gramos, de 92 nacidos muertos ó fallecidos antes de los 28 días de vida procedentes de gestaciones múltiples. Los datos se recogieron en un formulario siguiendo las recomendaciones de la FIGO y la novena Clasificación Internacional de Enfermedades (CIE). Resultados: La MP ampliada global fue de 40,42/1000 nacidos. Analizada por el número de RN, la MP de los embarazos gemelares fue 34,65/1000 nacidos y la de las gestaciones triples 80,65/1000. La mortalidad fetal fue 11,86/1000 nacidos y la neonatal (MN) 28,56/1000 nacidos vivos. La MP estándar fue 14,06/1000. Esta MP constituye el 22,89% de la MP total del Hospital, y la MN de los múltiples el 35,33% de la mortalidad neonatal total. Un 97,83% fueron pretérminos; 72,83% fueron <1000 gramos y 88,05% <1500 gramos. La causa última fue inmadurez extrema, <1000 gramos (72,83%). Hubo un 18,48% de rotura prematura (RPM) de membranas, 17,39% de partos pretérminos espontáneos sin otra causa aparente, y 13,04% de malformaciones congénitas y cromosomopatías. Conclusión: La MP en múltiples está gravada por la prematuridad, y el bajo peso extremo. La MP de ambos gemelos ocurre en el bajo peso extremo (87,50% <1000 gramos), y sus causas más frecuentes son RPM (21,88%) con corioam-nionitis (12,50%) y el síndrome de transfusión feto-fetal (18,76%). Objective: To evaluate Hospital Miguel Servet perinatal mortality (PM) in multiple pregnancies (2000-2009), valuing its evolution and distribution according to gestational age and birth weight. Maternal and fetal causes are analized. Methods: 44,401 newborns of >500 grams or 22 weeks gestational age, were studied. The total number of perinatal deaths in multiple pregnancies was 92 containing late neonatal deaths (to 28 days of live). The data for each case of perinatal mortality were recorded in a form following FIGO recommendations and the 9th International Classification Diseases. Results: Extended PM rate in multiple pregnancies was 40.42/1000 newborns, PM in twins was 34.65/1000, and in triplet births 80.65/1000. Fetal mortality was 11.86/1000 newborns and neonatal mortality 28.56/1000 live births. Standard PM was 14.06/1000 newborns. The MP of the multiple pregnancies was the 22.89% of total MP, and multiple pregnancies neonatal mortality 35.33% of total neonatal mortality. According to gestational age, 97.83% were preterm deliveries (90 newborns). Considering birth weights, 72.83% were extremely low birth weight (<1000 grams), and 88.05% were <1500 grams. Main cause of death was extreme immaturity (<1000 grams). Premature rupture of membranes (PROM) was presented in 18.48%, of the cases, spontaneous preterm labor without apparent cause in 17.39%, and congenital malformations and chromosomopaties (13.04%). Conclusions: PM in multiple pregnancies is encumbered by prematurity and extremely low birth weight. PM in both twins was associated with extremely low birth weight (87.50% < 1000 grams), and main causes of death were PROM (21.88%) with chorioamnionitis (12.50%), and twin-to-twin transfusion syndrome (18.76%).